Electrochemical reduction of CO2 to ethanol using copper nanofoam electrode and 1-butyl-3-methyl-imidazolium bromide as the homogeneous co-catalyst. Issue 3 (June 2019) - Zarandi, Reyhaneh Fazel; Rezaei, Behzad; Ghaziaskar, Hassan S.; Ensafi, Ali Asghar
Highlights: Carbon dioxide electrochemical reduction is an efficient way to produce fuels. Increasing catalyst activity may boost current efficiency for particular products. ILs, as well as suitable heterogeneous catalysts, increase faradic efficiency. A combination of a high surface area electrode and an IL used for CO2 conversion. They can lead to the production of more sophisticated products. Abstract: In this research, an electrochemical system, based on copper nanofoam accompanied by 1-butyl-3-methyl-imidazolium bromide (BMIMB) as the homogeneous co-catalyst for the electrochemical conversion of CO2 at ambient pressure and temperature was developed. Although, there have been some efforts for utilization of copper nanofoam or imidazolium-based catalysts toward the electro-reduction of CO2, evaluation of both catalysts to take advantage of the potential synergic effect of their combination would be an interesting aspect. The electroreduction of CO2 in a CO2 saturated 0.1 M KHCO3 electrolyte was optimized based on the highest CO2 conversion efficiency in various conditions. The results show that the copper nanoporous foam, deposited for 45 s with the contribution of 40 mM BMIMB at -1.6 V vs. Ag/ AgCl would effectively reduce CO2 and demonstrate a high CO2 faradaic efficiency i.e. more than 46% improvement, compared to similar previously reported experiment. The results confirm the applicability of this experiment as a developed method for efficient CO2 reduction.